IPSAS explained : a summary of international public sector accounting standards - Berger, Thomas Müller-Marqués (Wiley : Ernst & Young, 2012)
Global diversity in the practice of public sector accounting continues to impede the reduction of bureaucracy and the creation of comparable standards in terms of accountability and transparency. The International Public Sector Accounting Standards Board (IPSASB) continues to engage in the ongoing process of harmonizing public sector accounting with their International Public Sector Accounting Standards (IPSASs). IPSAS Explained: A Summary of International Public Sector Accounting Standards, Second Edition provides up to date information on the Conceptual Framework Project and other p.